2009
DOI: 10.1002/bdra.20523
|View full text |Cite
|
Sign up to set email alerts
|

Maternal asthma, asthma medication use, and the risk of congenital heart defects

Abstract: These results suggest that both maternal asthma status (controlled vs. uncontrolled; severe vs. mild) and asthma medication use, particularly bronchodilators, may play a role in cardiac malformations in offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 17 publications
1
45
2
Order By: Relevance
“…Our results are in line with previous human studies on short-term reproductive failures after asthma during pregnancy, which have shown associations of asthma during pregnancy with adverse obstetric outcomes and congenital malformation, [4][5][6] and extend knowledge to an overview of potential long-term consequences. Indeed, previous studies on long-term consequences of asthma during pregnancy with regard to selected child diseases also demonstrated an increased risk of asthma, bronchiolitis, atopic dermatitis, and autism spectrum disorder, in offspring of mothers with asthma.…”
Section: Figuresupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are in line with previous human studies on short-term reproductive failures after asthma during pregnancy, which have shown associations of asthma during pregnancy with adverse obstetric outcomes and congenital malformation, [4][5][6] and extend knowledge to an overview of potential long-term consequences. Indeed, previous studies on long-term consequences of asthma during pregnancy with regard to selected child diseases also demonstrated an increased risk of asthma, bronchiolitis, atopic dermatitis, and autism spectrum disorder, in offspring of mothers with asthma.…”
Section: Figuresupporting
confidence: 91%
“…5 Maternal asthma during pregnancy was also shown to play a role in cardiac malformations in the offspring. 6 However, the focus of these previous studies was on short-term adverse outcomes in the offspring, whereas long-term effects of maternal asthma on child health remain largely unknown. First studies on a narrow range of selected diseases suggest that maternal asthma during pregnancy is associated with an increased risk of asthma, 7,8 bronchiolitis, 9 atopic dermatitis, 10 and autism spectrum disorder 11 in the offspring during childhood, which is in line with animal models documenting intrauterine susceptibility to hypoxia-induced damage.…”
mentioning
confidence: 99%
“…Among the nine cohort studies that examined the association between maternal asthma and the risk of any congenital malformation (Alexander et al, 1998;Demissie et al, 1998;Dombrowski et al, 2004;Enriquez et al, 2007;Liu et al, 2001;Perlow et al, 1992;Schatz et al, 1995;Sobande et al, 2002;SteniusAarniala et al, 1996), only one reported a significantly greater risk among women with asthma (Demissie et al, 1998). The remaining case-control studies evaluated defects related to specific organ systems and even though they were limited in power, all of them reported a significantly greater risk for at least one specific congenital malformation among women with asthma (Lin et al, 2009;Tamasi et al, 2006;Tata et al, 2008). However, these three studies were impeded by other methodological weaknesses, such as the use of multiple testing without adjustment, recall bias, and earlier study periods resulting in a limited use of newer asthma controller therapies such inhaled corticosteroids (ICS) and long-acting inhaled beta 2 -agonists which are implicated in the current management of asthma (Lin et al, 2009;Tamasi et al, 2006;Tata et al, 2008).…”
Section: Introductionmentioning
confidence: 93%
“…The remaining case-control studies evaluated defects related to specific organ systems and even though they were limited in power, all of them reported a significantly greater risk for at least one specific congenital malformation among women with asthma (Lin et al, 2009;Tamasi et al, 2006;Tata et al, 2008). However, these three studies were impeded by other methodological weaknesses, such as the use of multiple testing without adjustment, recall bias, and earlier study periods resulting in a limited use of newer asthma controller therapies such inhaled corticosteroids (ICS) and long-acting inhaled beta 2 -agonists which are implicated in the current management of asthma (Lin et al, 2009;Tamasi et al, 2006;Tata et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis in the latter article found a weighted total odds ratio for a major malformation from four relatively large cohort studies of 1.18 (95% CI 1.00-1.36). Other studies used case-control approaches [4][5][6] and found statistically significant associations between maternal use of antiasthmatics and specific congenital malformations. As pointed out by many authors [2], a major problem in the interpretation of these results is the question of confounding by indication, that the underlying asthma and not the use of drugs caused the malformations.…”
Section: Introductionmentioning
confidence: 99%